3D DEM modeling on mechanical weakening of gas hydrate-bearing sandy sediments during hydrate dissociation. (February 2023) - Dou, Xiaofeng; Liu, Zhichao; Ning, Fulong; Li, Yanlong; Li, Xiaodong; Zhao, Yingjie; Hu, Wei; Gao, Deli
Abstract: The dissociation of natural gas hydrates (NGHs) during production weakens the mechanical properties of hydrate-bearing sediments (HBSs). Understanding and predicting the mechanical behaviors of HBSs is crucial for the safe development of NGH reservoirs. This study presents a novel approach based on the discrete element method (DEM) to describe the mechanical weakening of cementing-type gas hydrate-bearing sandy sediments (GHBSSs). Hydrate dissociation is simulated by reducing the parallel-bond radius based on a specific damage evolution law. The Weibull statistical distribution is incorporated into the model to characterize the heterogeneity of hydrates in GHBSSs. Subsequently, a series of numerical triaxial compression tests are conducted to investigate the mechanical weakening behavior of cementing-type GHBSSs and the mechanical effect of the heterogeneous distribution of hydrates. The results show that the DEM model can successfully capture the mechanical weakening behaviors of cementing-type GHBSSs during hydrate dissociation. The peak strength and secant modulus increase with increasing homogeneity index, but their sensitivities decrease as the hydrate dissociation ratio increases. Finally, a fitting equation describing the relationship among the peak strength, initial hydrate saturation, and hydrate dissociation ratio was obtained. This study is valuable for evaluating the stability of GHBSSs during hydrate production.